Business as Usual? Centering Human Rights to Advance Global COVID-19 Vaccine Equity Through COVAX - Kaitlin Fajber (Harvard FXB Center for Health and Human Rights, 2020)
This essay examines the extent to which COVID-19 Vaccines Global Access (COVAX) has been a successful mechanism for global COVID-19 vaccine equity as a component of the human right to health. First, I provide background on COVID-19 vaccine equity and COVAX as part of the Access to COVID-19 Tools ACT-Accelerator. Second, I situate access to COVID-19 vaccines within the context of human rights to exemplify how the international community intended COVAX to advance both health equity and the human right to health. Third, I assess how those intentions have played out in practice due to challenges of vaccine nationalism, lack of transparency, funding shortfalls, unreliable donations, inadequate civil society participation, and inequitable resource allocation. Fourth, I suggest how COVAX might function differently if human rights were centered within its purpose, strategy, and operations. Ultimately, I argue that COVAX is upholding a largely market-oriented approach to making essential medicines accessible and that COVAX would be a more effective mechanism for vaccine equity and global health if it were grounded in human rights.